PRELIMINARY CHARACTERIZATION OF CAVE SEDIMENTS IN KARSTIC SYSTEMS IN THE FIRST PLATEAU OF THE STATE OF PARANA, BRAZIL - SIRTOLI, Angelo Evaristo; de LIMA, Marcelo Ricardo (Scientia Agraria, 2002)
The soil in caves is formed largely by eroded sediments carried from the outside by rivers and precipitation of soluble substances. Organic materials from the surrounding ecosystems are also added to the sediments in caves. Agricultural and forestry activities in karstic areas may cause impacts in these caves. The purpose of this work was to evaluate chemical and granulometric characteristics of cave sediments, in three different karstic systems. The studied caves were the karstic systems of Bromado and Cachimba (Rio Branco do Sul PR) and Pinheirinho (Campo Largo PR). In most cases the pH of the sediments, are alkaline or slightly acidic. Higest levels of organic carbon are found in surface layers, in both current base levels and past base levels. Levels of available P are high, althought labile P fraction may also have been extracted. The K levels are medium to low. CEC and base saturation are high. The sediments are clayey and loamy. The highest concentrations of coarse sand are found in samples from the current base level, which may indicate degradation in areas surrounding the caves. These results may be used as indicators for assessing the human impacts in caves.